TARANTULAS (ARANAE: THERAPHOSIDAE) REPORTED FROM LORETO DEPARTMENT, PERU - RAMOS RODRIGUEZ, Maria Claudia (2024)
Tarantulas play a fundamental role as regulators of small animal populations, and are essential in studies of biodiversity, biogeography, animal behavior, and species trade. Despite their importance, there is a significant lack of information on tarantulas in the eastern Peruvian Amazon. To address this knowledge gap, we have compiled an exhaustive list of tarantula species present in the department of Loreto, using bibliographic data from publications such as scientific articles, books, theses, and conference abstracts. We reported a total of 42 tarantula species, corresponding to five subfamilies: Theraphosinae (with 30 species), Aviculariinae (with 6 species Psalmopoeinae (with 4 species), Schismatothelinae (with 1 species) and Ischnocolinae (with 1 specie), none of which are threatened in any conservation category. Of the eight provinces of the department of Loreto, Maynas reported the highest richness (with 21 species), followed by Putumayo (with 10 species), both sectors were the most studied in Loreto. Meanwhile, the Daten del Marañon province with at least 2 species. This information will be substantial for the development of effective conservation and management strategies for this important group of terrestrial invertebrates.